2015
DOI: 10.11114/jets.v3i4.774
|View full text |Cite
|
Sign up to set email alerts
|

Building Capacity for Research and Audit: Outcomes of a Training Workshop for Pacific Physicians and Nurses

Abstract: Building the research capacity of clinicians in the Pacific Island countries is important in addressing evidence gaps relevant to local policy and clinical practice. This paper aimed to assess the effectiveness of a reproductive health research workshop in increasing research knowledge and intention to perform research amongst a diverse group of clinicians. An online survey of clinicians and stakeholders in the Pacific Islands informed a research workshop curriculum. Physicians and nurses/midwives (n = 28) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Research capacity in nursing is commonly used at a non-individual level (one of the attributes we noted), suggesting that it is a concept used more with a macro perspective 32. However, because of the lack of a consistent definition of research capacity in nursing, a few researchers used research capacity in reference to research knowledge, skill and interest/attitude on the individual level 37 38. In those few cases, using the term ‘research competence and attitude’ might have been more suitable, based on the findings of this study which found that generally, research capacity in nursing was used at a non-individual level.…”
Section: Discussionmentioning
confidence: 86%
“…Research capacity in nursing is commonly used at a non-individual level (one of the attributes we noted), suggesting that it is a concept used more with a macro perspective 32. However, because of the lack of a consistent definition of research capacity in nursing, a few researchers used research capacity in reference to research knowledge, skill and interest/attitude on the individual level 37 38. In those few cases, using the term ‘research competence and attitude’ might have been more suitable, based on the findings of this study which found that generally, research capacity in nursing was used at a non-individual level.…”
Section: Discussionmentioning
confidence: 86%
“…Bissell et al [ 30 ] reported on two research courses, each with three 5-day modules; assessment of 24 participants at the end of 2 years found that 17 (71 %) completed the course and 18 manuscripts had been accepted for publication in peer-reviewed journals. In our study [ 20 ], comprised of a workshop of 7 days and supportive mentoring, only 18 (64 %) returned the assessment questionnaire and there were only two accepted publications. The participants’ clinical background was similar in both studies, although the majority of Bissell’s participants were from Fiji; both groups had access to experienced research mentors and online support.…”
Section: Discussionmentioning
confidence: 99%
“…The 28 study participants were clinicians selected from the leadership of the reproductive health services in six Pacific countries and criteria of selection have been previously published [ 17 , 20 ]. After a research workshop in March 2013, they were supported with assigned research mentors to work on research and clinical audit projects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 21 databased studies that were interventions, only two were controlled studies (28, 29) and one was a protocol of a controlled trial (30). Nine studies were post-intervention, cross sectional assessments without control arms (31)(32)(33)(34)(35)(36)(37)(38)(39), ve were prospective or retrospective cohorts, pre-post studies, or repeat cross sectional assessments (40)(41)(42)(43)(44) and four were reviews (45)(46)(47)(48).…”
Section: Methodsmentioning
confidence: 99%